Formulation and Evaluation of Nutraceutical Dosage form from Moringa oleifera, Amaranthus caudatus, and Fagopyrum esculentum - Saini, Ritu (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Recent years have seen a rise in the popularity of nutraceutical foods and related items as the importance of nutrition for health and wellness has come to light. Their potential health benefits, which extend beyond basic nutrition, make them extremely important in the control and management of health disorders. Nutraceutical foods are extremely rich in vital components, such as micronutrients, vitamins, minerals, and antioxidants. These components not only have a high nutritional value but also support healthy immune and physiological systems, which can help prevent disorders related to nutrition. Objectives: This study employs three potential crops – Fagopyrum esculentum, Amaranthus caudatus, and Moringa oleifera – to generate and assess nutraceutical granules. The exceptional nutritional profiles of these crops, which contain a range of bioactive compounds, amino acids, minerals, and vitamins, are well known. Materials and Methods: The granules were made using the wet granulation technique using different binders (potato and maize starch), and they were then examined for a number of assessment characteristics. Results: The nutraceutical granules showed improved physicochemical and micrometric capabilities compared to their powdered versions, the findings showed. It was found that the granules’ in vitro disintegration profile may reach 99.62%. Conclusion: Because of their exceptional mineral (iron) content, they are affordable and practical alternatives to the traditional formulations that are available for the therapy of nutritional problems such as iron deficiency anemia.